A method for preparing a lignin composite wood-based scaffold that can retain antioxidant bioactivity and have medical performance of tendon tissue regeneration
Patent Information
- Application Number
- CN202611190362.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-23
AI Technical Summary
现有木质素复合水凝胶多采用物理共混或化学交联方式制备,但物理共混可能存在木质素分散不均、易析出或易流失等问题,部分化学交联方式则存在反应条件复杂或影响生物相容性的可能
[0023](1)本申请首先以带有贯通纵向纤维孔道的轻木原木为基础制备获得脱木质素取向纤维素骨架基材,在这个基础上利用真空辅助浸润结合辣根过氧化物酶/H2O2温和酶促交联体系复合丝素蛋白与木质素,在木材内部连通孔道中原位生成稳定复合水凝胶网络,实现同时拥有仿生跟腱多尺度取向结构、优良细胞相容性、天然ROS清除抗氧化活性的一体化腱组织再生修复支架。
Smart Images

Figure CN122955028A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of biomedical composite materials and tendon tissue engineering materials, specifically relating to a method for preparing a lignin composite wood-based scaffold that can retain antioxidant bioactivity and possess tendon tissue regeneration medical properties. Background Technology
[0002] The Achilles tendon is an important weight-bearing tendon tissue in the human body, with a highly oriented collagen fiber structure. After acute or chronic Achilles tendon inflammation, degeneration, or injury, the local area is often accompanied by the release of inflammatory factors, increased oxidative stress, imbalance of extracellular matrix remodeling, and decreased mechanical load-bearing capacity. Traditional drug treatment, physical therapy, or surgical repair can alleviate symptoms to some extent, but they are still insufficient for simultaneously reconstructing the oriented structure of the Achilles tendon, improving the inflammatory microenvironment, and supporting the regeneration of tendon-related cells.
[0003] Hydrogel materials are widely used for soft tissue repair due to their high water content, tunable structure, and good cell compatibility. Silk fibroin is widely available, possesses good biocompatibility and processability; the horseradish peroxidase / hydrogen peroxide system can induce cross-linking of silk fibroin under mild conditions, making it suitable for constructing bioactive hydrogels. However, single hydrogels typically have limited mechanical strength and lack long-range orientation structures similar to tendon tissue. On the other hand, delignified wood retains the cellulose skeleton and pore structure aligned along the growth direction of natural wood, possessing natural anisotropy, and can be used as a biomimetic load-bearing framework to simulate tendon tissue orientation structures, but its own bioactivity and inflammation regulation capabilities still need to be enhanced.
[0004] Delignified wood retains the cellulose skeleton and longitudinally connected channels arranged along the growth direction of natural wood, exhibiting natural anisotropy, good structural stability, and processability. It can serve as a biomimetic load-bearing framework to mimic the oriented structure of tendon tissue. Existing technologies typically employ impregnation, vacuum-assisted impregnation, pressure-assisted impregnation, or in-situ polymerization to introduce hydrogel precursor solutions or polymeric materials into the channels of delignified wood. However, conventional impregnation methods may suffer from insufficient or uneven distribution of the precursor solution, or it may only adhere to the material surface; excessive filling can also cause channel blockage, affecting water transport and cell ingrowth. Furthermore, some composite systems using synthetic polymers or chemical cross-linking agents may have drawbacks such as harsh reaction conditions, difficulty in removing residual cross-linking agents, and insufficient biological activity.
[0005] Lignin contains active structural units such as phenolic hydroxyl groups, possessing certain free radical scavenging and antioxidant potential. Existing lignin-based composite hydrogels are mostly prepared using physical blending or chemical cross-linking methods. However, physical blending may suffer from uneven lignin dispersion, easy precipitation, or easy loss, while some chemical cross-linking methods may involve complex reaction conditions or affect biocompatibility. How to form a stable composite hydrogel of lignin and silk fibroin under mild conditions, and ensure its full penetration into the orientation channels of delignified wood while preserving the interconnected pores and anisotropic structure of the wood skeleton, remains a problem that needs to be solved by existing technologies.
[0006] Therefore, it is necessary to develop a composite scaffold that combines natural orientation structure, suitable mechanical properties, good cell compatibility, and the ability to regulate the microenvironment under oxidative stress, and to establish a mild, easy-to-operate, and easily controllable preparation method to meet the application needs of Achilles tendon inflammation repair and tendon tissue engineering. Summary of the Invention
[0007] The first technical problem solved by this invention is to provide a method for preparing a lignin-based composite wood-based scaffold that retains antioxidant bioactivity and possesses regenerative medical properties for tendon tissue. This method uses balsa wood logs with through-longitudinal pores to obtain a lignin-de-lignin oriented cellulose skeleton, which is then in-situ composited with a horseradish peroxidase / H2O2 mild crosslinking system within the wood pores to form a hydrogel network of silk fibroin and lignin. The second technical problem solved by this invention is to provide a scaffold obtained by the above method, which exhibits tunability in terms of mechanical toughness, water transport behavior, rheological response, and multi-scale anisotropy, and can be optimized by adjusting the silk fibroin concentration, lignin concentration, and intercalation time. The third technical problem solved by this invention is to provide the application of this oriented scaffold in the preparation of scaffold materials for Achilles tendon inflammation repair, tendon tissue regeneration, adjuvant treatment of tendon diseases, or tendon tissue engineering.
[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties involves preparing a delignified oriented cellulose wood skeleton from natural wood with through longitudinal channels along the fiber direction, and then continuously generating a lignin-silk fibroin composite hydrogel network in situ within the through channels of the oriented wood skeleton to obtain the lignin-based composite wood scaffold.
[0010] Furthermore, the natural wood is balsa wood, cut into shapes with a thickness of 1-10 mm and a width of 1-10 cm.
[0011] Furthermore, the delignification reagent used to prepare the delignified oriented cellulose wood skeleton is an aqueous solution of sodium chlorite and glacial acetic acid. The cut natural wood is immersed in the solution and boiled to complete the delignification treatment, removing protolignin and hemicellulose, while retaining the cellulose oriented skeleton and longitudinally connected channels.
[0012] Furthermore, the method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties includes the following steps:
[0013] 1) Select natural wood with through longitudinal channels along the fiber direction, cut it into shape along the wood fiber axis, and treat it with a water bath to remove the native lignin and hemicellulose of the wood, while retaining the cellulose orientation skeleton and longitudinal through channels to obtain delignified wood.
[0014] 2) Dissolve the regenerated silk fibroin powder in deionized water, add horseradish peroxidase solution and mix well, then add lignin powder and stir evenly to obtain lignin-silk fibroin hydrogel precursor solution.
[0015] 3) The delignified wood obtained in step 1) is completely immersed in the lignin-silk protein hydrogel precursor solution obtained in step 2), and the hydrogel precursor solution is introduced into the pores of the delignified wood skeleton; hydrogen peroxide solution is added to the system after immersion to carry out cross-linking reaction, and lignin composite wood-based scaffold is obtained.
[0016] Furthermore, in the lignin-silk fibroin composite hydrogel precursor solution, the lignin mass-volume concentration is 0.01-10 mg / mL; the regenerated silk fibroin concentration is 5-100 mg / mL.
[0017] Furthermore, the concentration of the horseradish peroxidase is 1000-10000 U / mL.
[0018] Furthermore, the mass concentration of the hydrogen peroxide is 0.001-5%.
[0019] Furthermore, the impregnation method is selected from at least one of static impregnation, vacuum-assisted impregnation, pressure-assisted impregnation, and centrifugal-assisted impregnation.
[0020] Furthermore, the method described above for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties yields a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties.
[0021] Furthermore, the lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties is used in the preparation of scaffold materials for Achilles tendon inflammation repair, tendon tissue regeneration, adjuvant treatment of tendon diseases, or tendon tissue engineering.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) This application first prepares a delignified oriented cellulose skeleton substrate based on balsa wood logs with through longitudinal fiber channels. On this basis, vacuum-assisted impregnation combined with a mild enzymatic crosslinking system of horseradish peroxidase / H2O2 is used to composite silk fibroin and lignin to generate a stable composite hydrogel network in situ in the through channels inside the wood. This achieves an integrated tendon tissue regeneration and repair scaffold that simultaneously possesses a biomimetic Achilles tendon multi-scale oriented structure, excellent cell compatibility, and natural ROS scavenging and antioxidant activity.
[0024] (2) This application has been experimentally proven to possess multiple quantifiable and excellent properties in the inflammatory microenvironment of Achilles tendon injury induced by TBHP-induced oxidative stress, exhibiting outstanding material mechanical anisotropy, with the longitudinal fracture strain of the high lignin group reaching 20% and the toughness reaching 150 MJ / m. 3 It combines load-bearing capacity and extensibility, and can completely preserve multi-scale orientation structure. The highest orientation parameter measured by SAXS / WAXS characterization can reach 0.94. The longitudinal capillary water absorption rate is significantly better than that in the transverse direction, and the anisotropy of water transport can be regulated. It has good biosafety performance, with cell survival rate of nearly 100% in all experimental groups and no obvious cytotoxicity. It has significant antioxidant effect. Among them, the SFWH-L0.15 group can significantly reduce the ROS fluorescence intensity in tendon-derived stem cells, effectively alleviating oxidative stress damage to cells. At the same time, it has excellent tendon differentiation promotion ability. Under oxidative stress conditions, the scaffold can significantly upregulate the fluorescence expression of two tendon differentiation markers, SCX and TNMD, and the relevant expression levels can be restored to near the standard of the normal blank group. It can guide tendon-derived stem cells to complete orderly adhesion, migration and differentiation into tendon cell lineages along the orientation channels of the scaffold. Attached Figure Description
[0025] Figure 1 The figures show the stress-strain curves, stress, strain, and toughness test results of different groups of composite stents under transverse and longitudinal tensile conditions in this application; where a is the longitudinal tensile stress-strain curve, b is the longitudinal tensile ultimate stress curve, c is the longitudinal tensile fracture strain curve, d is the longitudinal tensile toughness curve, e is the transverse tensile stress-strain curve, f is the transverse tensile ultimate stress curve, g is the transverse tensile fracture strain curve, and h is the transverse tensile toughness curve.
[0026] Figure 2 The images (a) and (b) are physical images of the DLW, SFWH and lignin-containing SFWH composite scaffolds of this application.
[0027] Figure 3 Fourier transform infrared spectra of different groups of composite stents in this application;
[0028] Figure 4 X-ray diffraction patterns of different groups of composite scaffolds in this application;
[0029] Figure 5 The figures show the rheological performance test results of different groups of composite stents in this application;
[0030] Figure 6 The figures show the test results of water transport process, absorption height and absorption rate of different groups of composite supports in this application under different wood orientations; where ab is the scheme and optical image of water transport process under different wood orientations, cd is the absorption height diagram under different transport orientations, and ef is the absorption rate curve under different transport orientations.
[0031] Figure 7 Images of different composite scaffolds of this application stained with toluidine blue under a polarizing microscope;
[0032] Figure 8 Figures show the characterization results of SAXS / WAXS multi-scale orientation structures of different groups of composite scaffolds in this application; where a is a two-dimensional scattering spot pattern of SAXS, b is a one-dimensional scattering intensity curve of SAXS, c is an azimuth integral curve of SAXS, d is a two-dimensional diffraction spot pattern of WAXS, e is a one-dimensional scattering intensity curve of WAXS, and f is an azimuth integral curve of WAXS.
[0033] Figure 9 Images of live / dead fluorescence staining and quantitative results of cell viability for different groups of composite scaffolds in this application are shown; where a is live / dead staining and b is the quantitative result of cell viability.
[0034] Figure 10 This image shows the results of intracellular ROS level detection in the TBHP-induced oxidative stress model of TDSCs after treatment with different groups of extracts in this application.
[0035] Figure 11 The images show the immunofluorescence and semi-quantitative results of the effects of different composite scaffolds on the expression of SCX and TNMD in TDSCs; where ab represents the immunofluorescence and semi-quantitative results of SCX, and cd represents the immunofluorescence and semi-quantitative results of TNMD. Detailed Implementation
[0036] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are implemented based on the technical solutions of the present invention, and it should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0037] The macroporous resin used in the following examples is XAD 16N, which was purchased from Yuanye Biotechnology Co., Ltd.
[0038] The lignin preparation method used in the following examples includes the following steps: 500 mL of pre-hydrolyzed solution is slowly added to a macroporous resin adsorption device, and after adsorption by the resin, deionized water is added to rinse the sugar solution, and then ethanol is added to rinse the lignin adsorbed on the resin to obtain a lignin solution; the lignin solution is concentrated by rotary evaporation and freeze-dried to obtain lignin.
[0039] The method for preparing regenerated silk fibroin used in the following examples includes the following steps: silk fibers are soaked in a 0.1-1% sodium carbonate solution for degumming, with a mass-to-volume ratio of silk to degumming solution of 1:10-1:200. The reaction is carried out at 100°C for 10-120 min, repeated 1-3 times. After the reaction, the fibers are washed with deionized water and dried to obtain degummed silk fibroin fibers. The degummed silk fibroin is added to a 9.3M lithium bromide solution and reacted at a mass-to-volume ratio of 1:5-30 at 40-90°C for 1-24 h. The mixture is then dialyzed through a dialysis bag with a molecular weight cutoff of 3-14 kDa and freeze-dried to obtain regenerated silk fibroin powder.
[0040] Example 1
[0041] Preparation of delignified wood skeleton: Natural balsa wood with longitudinal grain and continuous pore structure along the fiber is selected and cut into sheet, strip or column samples along the fiber growth axis, with the sample thickness controlled at 1-10 mm and width at 1-10 cm; a delignification treatment solution is prepared by mixing 5 g sodium chlorite, 0.5 mL glacial acetic acid and 195 mL deionized water, and 1 g of the cut balsa wood sample is completely immersed in the treatment solution and boiled in a water bath at 100 ℃ for 2 h to remove the protolignin and some hemicellulose of the wood, so as to obtain coarse delignified wood that retains the cellulose orientation skeleton and longitudinally connected pores; then the wood chips are thoroughly and repeatedly rinsed with deionized water until the washing solution is neutral to remove residual reagents. The washed delignified wood (DLW) can be used directly for subsequent intercalation while maintaining hydration, or it can be freeze-dried for later use.
[0042] Example 2
[0043] (1) Preparation of lignin-silk fibroin hydrogel intercalation orientation scaffold: Weigh 0.3 g of regenerated silk fibroin powder and dissolve it in 10 mL of deionized water. Add 50 μL of 10000U / mL horseradish peroxidase and mix gently to obtain silk fibroin hydrogel precursor solution.
[0044] (2) The lignin-free wood (DLW) prepared in Example 1 was completely immersed in the silk fibroin hydrogel precursor solution prepared in step (1). The precursor solution was fully filled into the wood pores by vacuum-assisted impregnation. The vacuum was set at -100 kPa for 20 min at room temperature and then slowly released to ensure that the precursor solution fully penetrated into the skeleton and left interconnected pores. After impregnation, 100 μL of 5% (w / w) hydrogen peroxide solution was added to the system to start the enzymatic cross-linking reaction. The reaction was carried out at 37°C for 24 h until the precursor solution was completely gelled, and the silk fibroin hydrogel intercalated DLW scaffold SFWH was obtained.
[0045] (3) After cross-linking, the obtained silk fibroin hydrogel intercalated DLW scaffold SFWH was washed in 0.01M PBS to remove unreacted components and stored at 4°C.
[0046] Example 3
[0047] (1) Preparation of lignin-silk fibroin hydrogel intercalation orientation scaffold: Weigh 0.3g of regenerated silk fibroin powder and dissolve it in 10mL of deionized water. Add 50μL of 10000U / mL horseradish peroxidase and mix gently to obtain silk fibroin hydrogel precursor solution. Then, add 3mg of lignin to obtain lignin-silk fibroin hydrogel precursor solution.
[0048] (2) The lignin-derived wood (DLW) prepared in Example 1 was completely immersed in the silk fibroin hydrogel precursor solution prepared in step (1). The precursor solution was fully filled into the wood pores by vacuum-assisted impregnation. The vacuum was set at -100 kPa for 20 min at room temperature and then slowly released to ensure that the precursor solution fully penetrated into the skeleton and left interconnected pores. After impregnation, 100 μL of 5% (w / w) hydrogen peroxide solution was added to the system to start the enzymatic crosslinking reaction. The reaction was carried out at 37°C for 24 h until the precursor solution was completely gelled, and the lignin-silk fibroin hydrogel intercalation DLW orientation scaffold SFWH-L0.03 was obtained.
[0049] (3) After cross-linking, the obtained lignin-silk protein hydrogel intercalation DLW orientation scaffold SFWH-L0.03 was washed in 0.01M PBS to remove unreacted components and stored at 4℃.
[0050] Example 4
[0051] The difference from Example 3 is that in step (1), the lignin mass is replaced with 30 mg to obtain lignin-silk fibroin hydrogel intercalation DLW orientation scaffold SFWH-L0.3.
[0052] Example 5
[0053] A method for preparing a lignin-silk fibroin hydrogel intercalated delignified wood orientation scaffold includes the following steps:
[0054] The difference from Example 3 is that in step (1), the lignin mass is replaced with 15mg to obtain lignin-silk fibroin hydrogel intercalation DLW orientation scaffold SFWH-L0.15.
[0055] The orientation scaffolds prepared in Examples 1-5 were frozen at -20°C for 48 hours, and then freeze-dried at -60°C for 48 hours. The relevant characterization results are as follows: Figures 1-8 As shown.
[0056] Depend on Figure 1 It can be seen that all scaffolds exhibit significant orientation dependence, with longitudinal tensile strength significantly higher than transverse tensile strength, indicating that the natural anisotropic structure of delignified wood is preserved after hydrogel intercalation. Under longitudinal tensile conditions, the DLW group has a higher ultimate stress, but the fracture strain is only about 5%, exhibiting obvious brittle fracture characteristics. After intercalation with silk fibroin hydrogel, the ultimate stress of the SFWH group decreased, but the fracture strain increased to about 13%, and the toughness increased from about 30 MJ / m. 3 Increased to approximately 70 MJ / m 3 This indicates that the flexible hydrogel phase can improve the deformation adaptability and energy dissipation capacity of the cellulose framework. Further introduction of lignin further enhances the longitudinal fracture strain and toughness of the scaffold. Specifically, the fracture strain of the SFWH-L0.03 group is approximately 18%, and the toughness is approximately 120 MJ / m. 3 The fracture strain of the SFWH-L0.3 group reached approximately 20%, and the toughness was approximately 150 MJ / m. 3 Meanwhile, its ultimate stress recovered to a level close to or slightly higher than that of the DLW group. This result indicates that the introduction of lignin can improve the synergistic load-bearing capacity between the hydrogel network and the cellulose skeleton to a certain extent, enabling the material to achieve better ductility and toughness while maintaining high load-bearing capacity. Under transverse tensile conditions, the fracture strain and toughness of each scaffold after intercalation with hydrogel were also higher than those of the DLW group, with the SFWH-L0.3 group showing the highest overall ultimate stress, fracture strain, and toughness. Combining the longitudinal and transverse test results, it can be seen that silk fibroin hydrogel mainly improves the ductility and energy dissipation capacity of the scaffold, while lignin can further regulate the load-bearing performance of the composite network. The high lignin addition group showed a better balance between strength and toughness.
[0057] Depend on Figure 2As can be seen from this, the DLW, SFWH, and low-lignin-added groups were generally white or milky white. With increasing lignin addition, the scaffold color gradually turned light yellow, indicating that lignin had been introduced into the composite scaffold. All samples maintained their intact blocky shape, and the hydrogel intercalation and cross-linking processes did not cause significant damage to the macroscopic structure of the lignin-de-ligninized wood. Figure 2 Scanning electron microscopy images (b) show that the DLW group retains long-range channels and a thin-walled cellulose skeleton arranged along the wood growth direction. After intercalation with silk fibroin hydrogel, the gel phase is observed to adhere to the pore walls and form connecting structures between some channels, indicating that the precursor solution has entered the interior of the DLW. After the addition of lignin, the gel network inside the channels becomes more obvious, and a more continuous interface is formed between the hydrogel and the cellulose skeleton. At the same time, each composite scaffold still retains a certain number of interconnected pores and is not completely sealed by the hydrogel. This structure is beneficial for load transfer between the hydrogel phase and the wood skeleton, and also preserves the necessary space for water transport, cell adhesion, migration, and ingrowth.
[0058] Depend on Figure 3 It can be seen that the DLW group is at approximately 3322 cm. -1 A broad absorption peak appears at [value missing], mainly related to the stretching vibrations of hydroxyl groups in cellulose and residual hemicellulose. After intercalation with silk fibroin hydrogel, this broad peak shifts to approximately 3279 cm⁻¹. -1 This suggests that strong hydrogen bond interactions may have formed between silk fibroin, the hydrogel network, and the cellulose backbone. The composite scaffold is approximately 1640 cm⁻¹. -1 A distinct absorption peak appears at approximately 1730 cm⁻¹, which can be attributed to the amide I band of silk fibroin, indicating that the silk fibroin component has been successfully introduced into the DLW channel. -1 The nearby absorptions are related to the carbonyl structure in the material, possibly originating from residual hemicellulose and lignin-related structures. Changes in the characteristic peak intensity and shape of different lignin addition groups indicate that the introduction of lignin alters the intermolecular interactions of the composite system. These results support the inclusion of silk fibroin and lignin components in delignified wood, but infrared spectroscopy alone is insufficient to definitively prove the formation of a specific type of covalent bond.
[0059] Depend on Figure 4It was observed that the characteristic diffraction peaks of cellulose type I crystals (101) and (002) appeared at approximately 16° and 22° for all samples. Furthermore, no obvious new crystal form diffraction peaks were observed after the introduction of hydrogel and lignin, indicating that the intercalation treatment did not change the basic crystal form of the cellulose skeleton. The crystallinity index of the DLW group was 90.5%, while after intercalation with silk fibroin hydrogel, the crystallinity index of the SFWH group decreased to 73.5%, indicating that the introduction of the amorphous hydrogel phase reduced the overall apparent crystallinity of the composite material. After the addition of lignin, the crystallinity indices of the SFWH-L0.03 group and the SFWH-L0.3 group were 85.1% and 84.6%, respectively, both higher than the SFWH group but still lower than the DLW group. This result indicates that the introduction of lignin can affect the hydrogel network and its assembly state with the cellulose skeleton, allowing the composite scaffold to maintain the cellulose type I crystal structure while exhibiting different degrees of order.
[0060] Depend on Figure 5 It can be seen that within the stress scanning range of approximately 10–1000 Pa, the storage modulus G′ of each group of samples is consistently higher than the loss modulus G″, indicating that each material exhibits a predominantly elastic response and a stable, solid-like network structure. The DLW group has the highest G′, which remains relatively stable within the testing range, reflecting the strong rigid support provided by the cellulose skeleton. After intercalation with silk fibroin hydrogel, both G′ and G″ of the SFWH group are lower than those of the DLW group, indicating that the introduction of the flexible hydrogel phase reduces the overall stiffness of the material. After the addition of lignin, the G′ and G″ of the SFWH-L0.03 and SFWH-L0.3 groups were both higher than those of the SFWH group. The modulus of the SFWH-L0.03 group was higher than that of the SFWH-L0.3 group, indicating that an appropriate amount of lignin can enhance the composite hydrogel network. However, this enhancement effect does not increase monotonically with increasing lignin content. In higher stress regions, the G′ of the composite scaffold gradually decreased, suggesting that the hydrogel network undergoes a certain degree of structural rearrangement or softening under high stress. Overall, lignin can modulate the viscoelasticity of the composite scaffold, with the low lignin addition group exhibiting a more significant modulus enhancement effect.
[0061] Depend on Figure 6It was observed that all scaffolds exhibited significant direction-dependent water transport behavior. Along the longitudinal pores of cellulose, the DLW group showed the fastest liquid rise rate and the highest final water absorption height, indicating that the naturally connected longitudinal pores possess strong capillary transport capabilities. After intercalation with silk fibroin hydrogel, the initial water absorption rate and final water absorption height of the SFWH group decreased, indicating that the hydrogel occupying part of the longitudinal pores increased the resistance to water migration. The addition of lignin further altered the longitudinal water transport performance. The SFWH-L0.03 group was similar to the SFWH group, while the water absorption height and rate of the SFWH-L0.3 group recovered somewhat but remained lower than the DLW group, indicating that the amount of lignin added could regulate the gel network state and the water migration process within the pores. In the transport direction perpendicular to the longitudinal pores of cellulose, the water absorption height of each group was significantly lower than in the longitudinal transport direction. The lateral water absorption height and initial water absorption rate of the SFWH group were higher than those of the DLW group, suggesting that the continuous hydrogel phase may have established new water migration pathways between adjacent pores. As the water absorption process proceeds, the water absorption rate of each group gradually decreases and approaches zero, consistent with the characteristic of capillary water absorption gradually reaching equilibrium. These results indicate that the composite scaffold, while retaining directional water transport characteristics, can regulate longitudinal and lateral water migration behavior through the hydrogel and lignin content.
[0062] Depend on Figure 7 It can be seen that the DLW, SFWH, SFWH-L0.03, and SFWH-L0.3 groups all exhibit continuous, parallel banded structures. When the samples are rotated sequentially from 0° to 45°, 90°, and 135°, the orientation texture in the images changes synchronously with the sample angle, showing direction-related changes in brightness and color, indicating that each group of samples has obvious anisotropy. After intercalation with silk fibroin hydrogel and further addition of lignin, the original long-range orientation texture of the wood remains clearly visible, without significant disorder or disappearance. This indicates that the hydrogel filling mainly occurs inside the pores of the delignified wood and does not disrupt the macroscopic orientation arrangement of the cellulose skeleton.
[0063] Depend on Figure 8 As can be seen from a, the SAXS two-dimensional scattering patterns of each group of samples all show spindle-shaped or rhomboid scattering patterns concentrated along a specific direction, indicating that the material has obvious orientation at the nanoscale. Figure 8 The azimuth integral curves of c all showed obvious peaks at approximately 90° and 270°; the orientation parameters r for the DLW, SFWH, SFWH-L0.03, and SFWH-L0.3 groups were approximately 0.86, 0.88, 0.87, and 0.82, respectively. All groups maintained a high degree of orientation, but the orientation parameters of the high-lignin-added groups decreased slightly, which is related to the influence of more gel phase entering the pores on the local structural order. Figure 8As shown in d~f, the WAXS two-dimensional diffraction patterns of each group retain obvious directional diffraction arcs and exhibit characteristic diffraction peaks of the (110), (200), and (004) crystal planes of cellulose crystals, indicating that the cellulose crystal structure was not destroyed by the intercalation treatment. The orientation parameters of the WAXS azimuth integral curves are approximately 0.93, 0.94, 0.93, and 0.89, respectively, indicating that each group also has a high degree of orientation at the molecular and crystal scales. The SAXS and WAXS results together prove that the introduction of silk fibroin hydrogel and lignin did not significantly destroy the original multi-scale orientation structure of DLW.
[0064] Example 5
[0065] DLW, SFWH, SFWH-L0.03, SFWH-L0.15, and SFWH-L0.3 scaffolds were cut to the same size, sterilized by immersion in 75% ethanol, and thoroughly washed with sterile PBS. Each group of scaffolds was immersed in complete culture medium at a scaffold-to-culture medium volume ratio of 0.1 g / mL and extracted at 37 ℃ for 24 h. The extract was collected for later use. Tendon-derived stem cells (TDSCs) from generations P1 to P3 were seeded in 12-well plates and cultured at 37 ℃ with 5% CO2 for 24 h. After cell adhesion, further processing was performed. The experiment included a blank control group, a TBHP model control group, and four subgroups: DLW, SFWH, SFWH-L0.03, SFWH-L0.15, and SFWH-L0.3.
[0066] TDSCs were co-cultured with scaffold extracts for 24 h, respectively. The culture medium was discarded, and the cells were washed with PBS. Calcein-AM and PI working solutions were added according to the kit instructions, and the cells were incubated at 37 °C in the dark for 30 min. Fluorescence microscopy was used for observation. Calcein-AM labeled live cells showed green fluorescence, while PI labeled dead cells showed red fluorescence. Images were taken from at least 3-5 randomly selected fields of view for each group. The number of live cells and dead cells were counted, and cell viability was calculated as "live cells / total cells × 100%". Figure 9 As shown in Figure a, the blank group, DLW group, SFWH group, and groups with different lignin addition levels all showed predominantly green live cell fluorescence signals, with only a small amount of red dead cell signals observed. The cells were relatively evenly distributed in each group, and no obvious cell aggregation, shedding, or large-scale death was observed. Figure 9Quantitative results (b) showed that the cell viability of each material group was close to 100%, comparable to the control group, and no significant increase in cell death rate was observed with increasing lignin addition. These results indicate that delignified wood, silk fibroin hydrogel, and different amounts of lignin did not produce significant cytotoxicity under the experimental conditions described. Hydrogel intercalation and lignin introduction did not disrupt the original cell compatibility of the materials, and the resulting composite scaffold provides a good biological basis for subsequent evaluation of antioxidant properties and tendon-related phenotypes. It should be noted that live / dead staining mainly reflects the effect of the material on cell survival and cannot alone prove that the material can promote cell proliferation.
[0067] After TDSCs adhered to the culture medium, the culture medium was replaced with the scaffold extract for each group and pretreated for 24 h. Except for the control group, all other groups were treated with TBHP at a final concentration of 100 μmol / L for 6–8 h to establish a cellular oxidative stress model. After treatment, DCFH-DA working solution was added, and the cells were incubated at 37 ℃ in the dark for 30 min, followed by washing three times with serum-free medium or PBS. Fluorescence images were acquired using the same exposure parameters, with at least 3–5 fields of view randomly selected from each group, and the average fluorescence intensity was calculated using software such as ImageJ.
[0068] like Figure 10 As shown, the blank group without TBHP treatment only showed a weak green ROS fluorescence signal; the TBHP model control group showed a large amount of strong green fluorescence, and the three-dimensional fluorescence intensity map also showed dense and high peaks, indicating that TBHP treatment led to a large accumulation of ROS in TDSCs, and the oxidative stress model was successfully constructed. Compared with the TBHP model control group, the ROS fluorescence intensity of the DLW group was reduced, but still remained at a high level, indicating that the effect of delignified wood itself on improving intracellular ROS accumulation was relatively limited. The ROS fluorescence signal of the SFWH group was further reduced, suggesting that the silk fibroin hydrogel microenvironment may alleviate TBHP-induced oxidative stress to some extent. After the addition of lignin, the ROS fluorescence signals of the SFWH-L0.03, SFWH-L0.15, and SFWH-L0.3 groups were significantly lower than those of the TBHP model control group, DLW group, and SFWH group. Among them, the SFWH-L0.15 group had the lowest overall fluorescence signal, and the number and height of the three-dimensional fluorescence intensity peaks were also significantly reduced. When the lignin addition was further increased to 0.3%, the ROS fluorescence signal did not continue to decrease, indicating that the effect of lignin in reducing intracellular ROS levels may have an appropriate addition range, rather than being linearly enhanced with the increase of addition.
[0069] Lignin contains active structural units such as phenolic hydroxyl groups, which participate in free radical reactions by donating hydrogen atoms or electrons. Therefore, its introduction is an important reason why lignin-containing scaffolds reduce intracellular ROS accumulation. The above results indicate that lignin-silk fibroin hydrogel intercalation scaffolds have the ability to improve the cellular oxidative stress microenvironment, with the SFWH-L0.15 group showing a better ROS reduction effect under the experimental conditions. Since ROS fluorescence detection cannot distinguish between direct ROS scavenging and ROS generation inhibition, the text should describe it as "reducing intracellular ROS levels," and the specific mechanism of action should not be determined solely based on this experiment.
[0070] After treatment with extract and TBHP, cells in each group were washed with PBS and fixed with 4% paraformaldehyde for 30 min; permeabilized with 0.1% Triton X-100 for 30 min, and then blocked with 5% BSA at room temperature for 1 h. Primary antibodies SCX and TNMD were added and incubated overnight at 4 ℃. The manufacturers, catalog numbers, and dilution ratios of the primary antibodies were Abimart, PC12364, PC41215, and 1:200, respectively. The next day, after washing, the corresponding fluorescently labeled secondary antibodies were added, and the cells were incubated in the dark for 1 h, followed by counterstaining of the cell nuclei with DAPI. Images were acquired using the same microscope parameters, and at least 3-5 fields of view were randomly selected from each group. The average fluorescence intensity per unit cell or unit area was calculated using software such as ImageJ. Figure 11 As shown in a and b, the blank group exhibited a strong green SCX fluorescence signal. After TBHP treatment, SCX expression in the model control group significantly decreased, indicating that oxidative stress significantly inhibited the tendon-related phenotype of TDSCs. SCX expression in the DLW group only slightly increased, with a relatively small difference compared to the model control group; the SCX fluorescence intensity in the SFWH group further increased, indicating that silk fibroin hydrogel treatment could improve SCX expression under oxidative stress conditions to some extent. With the introduction of lignin, SCX expression showed a further increasing trend. The SCX fluorescence intensity in the SFWH-L0.03 group was higher than that in the SFWH group, and the SCX expression in the SFWH-L0.15 and SFWH-L0.3 groups reached or slightly exceeded the level of the blank group, with small differences between the two groups. This indicates that an appropriate amount of lignin can enhance the ability of the composite scaffold to maintain SCX expression, but when the lignin content reaches a certain level, this effect gradually plateaus. Figure 11As shown in c and d, TNMD expression generally showed a similar trend to SCX. The blank group had a strong red fluorescence signal of TNMD, while TNMD expression in the TBHP model control group was significantly reduced; the DLW group showed only a slight recovery, and TNMD expression in the SFWH and SFWH-L0.03 groups was increased. The TNMD fluorescence intensity of the SFWH-L0.15 and SFWH-L0.3 groups was significantly higher than that of the model control group, DLW group, SFWH group, and SFWH-L0.03 group, and approached the level of the blank group. There was no further trend of continuous increase with increasing lignin addition between the SFWH-L0.15 and SFWH-L0.3 groups. SCX is an important transcription factor in tendon cell fate determination and tendon-related differentiation, and TNMD is an important marker reflecting the mature phenotype of tendon cells. The results indicate that TBHP-induced oxidative stress can significantly inhibit the expression of SCX and TNMD in TDSCs, while lignin-silk fibroin hydrogel intercalation scaffolds can improve this inhibition to varying degrees, with the SFWH-L0.15 and SFWH-L0.3 groups showing the most significant effects.
[0071] Comparative Example 1
[0072] The difference between this application and CN122208516A is not only in their different uses. CN122208516A mainly relates to the lignin-silk fibroin hydrogel itself, while this application further introduces delignified wood with longitudinally interconnected channels on the basis of the hydrogel, and introduces the lignin-silk fibroin hydrogel precursor liquid into the delignified wood channels through impregnation treatment, and cross-links in situ inside the channels to form a composite orientation scaffold composed of the delignified wood oriented cellulose skeleton and the lignin-silk fibroin hydrogel.
[0073] Specifically, the single hydrogel described in CN122208516A mainly relies on the hydrogel network to provide bioactivity and a moist microenvironment, but it usually lacks a long-range orientation structure similar to Achilles tendon collagen fibers, and its mechanical load-bearing capacity, orientation dependence, and ability to guide cell orientation growth are limited. This application utilizes the longitudinal cellulose skeleton and connecting channels retained from delignified wood to construct a macroscopic orientation framework, and fills these orientation channels with a lignin-silk fibroin hydrogel. This allows the wood skeleton to provide structural support, the hydrogel phase to provide cell compatibility and a flexible microenvironment, and the lignin to endow the material with the ability to reduce intracellular ROS levels.
[0074] This application demonstrates a synergistic effect through the composite of a hydrogel phase and a delignified wood orientation scaffold. Experimental results show that after the hydrogel enters the pores of the delignified wood, the material retains the multi-scale orientation structure and interconnected pores of natural wood. Compared with delignified wood alone, the composite scaffold exhibits improved deformation adaptability and toughness. The scaffold also displays orientation-dependent water transport behavior, providing a structural basis for the orientational adhesion and migration of tendon-related cells. Further introduction of lignin reduces intracellular ROS levels in a TBHP-induced oxidative stress model and improves the expression of SCX and TNMD, indicating that it possesses structural guidance, mechanical support, and oxidative stress regulation functions.
[0075] Therefore, this application focuses on solving the technical problems of single hydrogels lacking long-range orientation structure, insufficient structural support strength, and inability to simulate the anisotropic microenvironment of the Achilles tendon while retaining the bioactivity and antioxidant properties of lignin-silk fibroin hydrogels. This application achieves a composite scaffold with multi-scale orientation structure, adjustable water transport, good deformation adaptability, cell compatibility, and ROS regulation capability through a composite design of "delignified wood-oriented framework - in-situ cross-linking of hydrogel within pores - lignin active components." Therefore, it has a clear structural difference and functional advantages compared to CN122208516A.
[0076] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses regenerative medical properties for tendon tissue, characterized in that, A delignified oriented cellulose wood skeleton was prepared from natural wood with through longitudinal channels along the fiber direction. Then, a lignin-silk fibroin composite hydrogel network was continuously generated in situ inside the through channels of the oriented wood skeleton to obtain a lignin composite wood-based scaffold.
2. The method for preparing a lignin-based wood composite scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 1, characterized in that: The natural wood is balsa wood, cut into shapes with a thickness of 1-10 mm and a width of 1-10 cm.
3. The method for preparing a lignin-based wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 1, characterized in that: The delignification reagent used to prepare delignified oriented cellulose wood skeleton is an aqueous solution of sodium chlorite and glacial acetic acid. The cut natural wood is immersed in the solution and boiled to complete the delignification treatment, removing protolignin and hemicellulose, while retaining the cellulose oriented skeleton and longitudinally connected channels.
4. The method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to any one of claims 1-3, characterized in that: Includes the following steps: 1) Select natural wood with through longitudinal channels along the fiber direction, cut it into shape along the wood fiber axis, and treat it with a water bath to remove the native lignin and hemicellulose of the wood, while retaining the cellulose orientation skeleton and longitudinal through channels to obtain delignified wood. 2) Dissolve the regenerated silk fibroin powder in deionized water, add horseradish peroxidase solution and mix well, then add lignin powder and stir evenly to obtain lignin-silk fibroin hydrogel precursor solution. 3) The delignified wood obtained in step 1) is completely immersed in the lignin-silk protein hydrogel precursor solution obtained in step 2), and the hydrogel precursor solution is introduced into the pores of the delignified wood skeleton; hydrogen peroxide solution is added to the system after immersion to carry out cross-linking reaction, and lignin composite wood-based scaffold is obtained.
5. The method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 4, characterized in that: In the lignin-silk fibroin composite hydrogel precursor solution, the lignin mass-volume concentration is 0.01-10 mg / mL; the regenerated silk fibroin concentration is 5-100 mg / mL.
6. The method for preparing a lignin-based wood-based scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 4, characterized in that: The concentration of horseradish peroxidase is 1000-10000 U / mL.
7. The method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 4, characterized in that: The mass concentration of the hydrogen peroxide is 0.001-5%.
8. The method for preparing a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties according to claim 4, characterized in that: The impregnation method is selected from at least one of static impregnation, vacuum-assisted impregnation, pressure-assisted impregnation, and centrifugation-assisted impregnation.
9. The lignin-based composite wood scaffold prepared by the method of claim 1, which retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties, is a lignin-based composite wood scaffold that retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties.
10. The application of the lignin composite wood-based scaffold of claim 9, which retains antioxidant bioactivity and possesses tendon tissue regeneration medical properties, in the preparation of scaffold materials for Achilles tendon inflammation repair, tendon tissue regeneration, adjuvant treatment of tendon diseases, or tendon tissue engineering.
Citation Information
Patent Citations
Modified lignin-silk fibroin injectable hydrogel as well as preparation method and application thereof
CN122208516A